Impact of Metaverse in Educational Environment - Rahman, Misran; Attaufiq, Muhammad Muhdi; Setiyowati, Endah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this review is to define of metaverses and to explain their potential and limitations for pedagogical applications in educational environment. The Metaverse has infinite possibilities as a new social communication space. . In other words, the Metaverse is a post-reality universe, an eternal and permanent multi-user environment that combines physical reality and digital virtuality. Regarding the educational use of the metaverse, the following future tasks are proposed: First, teachers need to carefully analyze how students understand the metaverse. Next, teachers should design classes that encourage students to collaboratively and creatively solve problems and complete projects. Third, a educational metaverse platform should be developed to prevent the misuse of student data.